Providing harmonization of financial and tax accounting of corporate income: a theoretical and methodical aspect - Serhiy Bogachov (Cхід, 2016)
The purpose of the article is to explore and generalize a theoretical and methodical basis for the harmonization of financial and tax accounting of corporate income.